2016
DOI: 10.1089/jmf.2016.3665
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry (Morus alba L.) Fruit Extract Containing Anthocyanins Improves Glycemic Control and Insulin Sensitivity via Activation of AMP-Activated Protein Kinase in Diabetic C57BL/Ksj-db/db Mice

Abstract: The effect of mulberry (Morus alba L.) fruit extract (MFE) on hyperglycemia and insulin sensitivity in an animal model of type 2 diabetes was evaluated. C57BL/Ksj-diabetic db/db mice were divided into three groups: diabetic control, rosiglitazone, and MFE groups. Blood glucose, plasma insulin, and intraperitoneal glucose were measured, and an insulin tolerance test was performed after MFE supplementation in db/db mice. In addition, the protein levels of various targets of insulin signaling were measured by wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…In this regard, the various effect of monoterpenes in signaling pathways appear to be consistent with antidiabetic effect through upregulation of GLUT4 expression and/or translocation ( Table 1 ). The modulation of the AMPK pathway by natural products that enhance glucose uptake while concomitantly inhibiting gluconeogenesis and stimulation of glycogen synthesis have previously been reported (e.g., [ 128 , 129 , 130 , 131 , 132 ]. Hence, possible multiple mechanisms involving insulin signaling and other pathways involving the AMPK, GLUT4 and PPARγ are at play in the antidiabetic effect of monoterpenes.…”
Section: General Summary and Discussionmentioning
confidence: 99%
“…In this regard, the various effect of monoterpenes in signaling pathways appear to be consistent with antidiabetic effect through upregulation of GLUT4 expression and/or translocation ( Table 1 ). The modulation of the AMPK pathway by natural products that enhance glucose uptake while concomitantly inhibiting gluconeogenesis and stimulation of glycogen synthesis have previously been reported (e.g., [ 128 , 129 , 130 , 131 , 132 ]. Hence, possible multiple mechanisms involving insulin signaling and other pathways involving the AMPK, GLUT4 and PPARγ are at play in the antidiabetic effect of monoterpenes.…”
Section: General Summary and Discussionmentioning
confidence: 99%
“…The AMPK pathway has also been emerged as a major drug target for diabetes and related diseases given its crucial regulatory role in energy metabolism involving glucose and lipids [ 140 ]. The increased phosphorylation of the AMPK pathway by anthocyanin such as those from mulberry fruit extract could not only increase glucose uptake but also inhibit gluconeogenesis and stimulates glycogen synthesis [ 141 ]. The improvement of glucose homeostasis in diabetic mice by cyanidin-3- O -β-glucoside [ 142 ] and dietary anthocyanin-rich bilberry extract [ 67 ] has been shown to be mediated through activation of the AMPK pathway.…”
Section: General Summary and Conclusionmentioning
confidence: 99%
“…It was also reported that an M. alba leaf extract-containing diet could reduce insulin resistance and may delay the development of diabetes [ 19 ]. Fruit extract from M. alba improved hyperglycemia and insulin sensitivity via activation of the adenosine 5′-monophosphate (AMP)-activated protein kinase (AMPK) and AS160 in skeletal muscles and inhibition of gluconeogenesis in the liver [ 20 ]. Similarly, it was reported that a 70% alcohol extract of M. alba root bark could protect the generation of pancreatic β-cells, and a leaf extract could restore diminished β-cell numbers [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%